Utilizing of recycle papers as an acoustic treatment in building / Muhamad Nazreen Zulkufli - Zulkufli, Muhamad Nazreen (Faculty Architecture, Planninng and Surveying, 2014)
Sound pollution always becomes the major concern to many people especially in urban area. Usually, the expensive sound absorbance materials are used to solve this disturbance. Recycled material has many advantages as absorbance material compared to the conventional panels because it can reduce product cost, good handling, and environmental protection. This study discusses the viability of recycled papers to be implemented as sound absorption panel. The study was carried out on the use of by-product from recycle material which has common use in daily life which is paper. The chosen of recycled paper are known for its soft and absorbance properties and easy to be use and reformed. The recycled papers being undergo a shredded process into pieces and also the clumped process. Then, it will be inserted into 100cm x 100m square framed panel to be tested. There are three samples were used in this study which is empty panel as the controlled parameter,panel with shredded paper and panel with clumped paper. The reverberant room method use in this research was referred to the standard by ASTM C423 to obtain the acoustic properties of the samples. For the test, it was carried out at mini sound transmission chamber located at Faculty of Architecture, Planning & Sun/eying in UiTM Shah Alam. From the test, it show sample 3 which is panel with the clumped paper display the most good results compared with other samples. Sample 3 (Clumped Paper) shows the Noise Reduction Coefficient (NRC) with the reading 0.90 a, that is fall in the class ‘A’ which is the value range from 0.90 to 1.00 of the sound absorbance rating by Baumann (2001). Furthermore, according to the standard provide by ASTM C423 & F2154, the sample 3 (clumped paper) has already achieved the minimum sound absorption coefficient from the ASTM which the minimum requirement for 2inch (50.8mm) panel is 0.80a and absorption coefficient for sample 3 is 0.90. This shows the good potential of recycled paper to be used as sound absorbance panel. Overall of the results demonstrate good acoustics performances and highlight the potential of recycled papers as the sound absorption panel